2019
DOI: 10.1109/access.2018.2889724
|View full text |Cite
|
Sign up to set email alerts
|

New Analytical Capacitance Modeling of the Perforated Switch Considering the Fringing Effect

Abstract: Movable suspended microstructures are common features of sensors and devices in the field of micro electro mechanical systems (MEMS). This paper addresses the study of approach to model the capacitance for the crab-type meander-based RF MEMS shunt switch with etching holes on the beam. The presented paper evaluates the parallel-plate capacitance and fringing-field capacitance caused by the etching holes on the beam and introduces empirical formulae. From the literature study, an accurate empirical formula is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…It can be observed that for all the different junction areas, the theoretical curve is shifted downward by a constant equal to 5 fF. The difference between the dotted line for C j th and the actual measurement data can be caused due to a parasitic capacitance generated by leakage of electric field at the edges of the diodes' intrinsic region toward the neighboring layers of the collector layer forming a fringe capacitor in parallel to C j [85][86][87]. In summary, the classical method of open-short provides both the R s and C j at the price of adding a virtual inductance (L p ) with reduced values for R s in high frequencies leading to an imprecise circuit model of the intrinsic area within the photodetectors.…”
Section: Comparison Koolencorrectedmentioning
confidence: 90%
“…It can be observed that for all the different junction areas, the theoretical curve is shifted downward by a constant equal to 5 fF. The difference between the dotted line for C j th and the actual measurement data can be caused due to a parasitic capacitance generated by leakage of electric field at the edges of the diodes' intrinsic region toward the neighboring layers of the collector layer forming a fringe capacitor in parallel to C j [85][86][87]. In summary, the classical method of open-short provides both the R s and C j at the price of adding a virtual inductance (L p ) with reduced values for R s in high frequencies leading to an imprecise circuit model of the intrinsic area within the photodetectors.…”
Section: Comparison Koolencorrectedmentioning
confidence: 90%
“…For example, the reduction in squeezefilm damping improves the operation speed of switches and other devices [1] and optimizes the drive voltage and sensitivity of capacitive micro-machined ultrasonic transducers [2]. Another example is the improvement in the operating speed or the vibration resistance by increasing the resonance frequency through mass reduction [3]. In other words, the technology used to estimate the effect of release-etch holes is becoming more important.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various studies have been conducted on this topic. For example, Rao et al proposed a capacitance model for radiofrequency (RF) switches [3], and Abdelrahman et al developed a model for the static displacement of a beam with an etch hole that considers the microstructural effect [8]. The equivalent mechanical properties of perforated structures have also been studied [9,10].…”
Section: Introductionmentioning
confidence: 99%